(untitled) - Wright, Erik Olin (Cambridge, U.K.,New York, 2000)
This textbook provides a lively and penetrating exploration of the concept of class and its relevance for understanding a wide range of issues in contemporary society. The book presents a sophisticated account of the theoretical foundations in an accessible and engaging manner. It then explores class using cross-national comparative data on topics such as social mobility, housework, friendship patterns, class structure and class consciousness. This Student Edition of Class Counts thus combines Wright's sophisticated account of central and enduring questions in social theory with practical analyses of detailed social problems
Keywords: Social classes,Social mobility,Class consciousness,Giai cấp xã hội,Quá trình biến đổi xã hội